Methodological studies of health research - Lawson, Daeria (My University, 2023)
Methodological studies of health research are undertaken to investigate the practice of research. They have been instrumental in inciting developments in the design, conduct, analysis, and reporting of health research. Due in part to the field’s diversity, these studies can be difficult to identify in databases. As these studies have not been comprehensively examined to date, the overarching goal of this thesis was to characterize methodological studies and to investigate how they have been labelled and reported in the literature. First, we demonstrate how methodological studies are conducted to provide guidance to end-users—in this case physiatrists and rehabilitation researchers—in a methods guidance paper on pilot and feasibility studies (PAFS), a type of health research design. Second, we performed a pilot study testing the feasibility of searching for and identifying methodological studies in literature databases. Third, based on the pilot study findings and previous research, we outline a protocol for the development of a reporting guideline for methodological studies of health research. Lastly, as part of the first phase of the reporting guideline development process, we performed a review of methodological studies focusing on those that specifically investigated PAFS. In a case study of rehabilitation research, a third of studies labelled as PAFS did not outline any feasibility outcomes, and few provided progression plans to definitive studies. Guidance was focused on providing recommendations and resources for assessing feasibility to help reduce the prevalence of small studies disguised as PAFS, which wastes research resources. In the pilot of methodological studies, preliminary findings on nomenclature and reporting reinforced the notion that there are many names used to describe studies with similar intentions. It was also determined feasible to build a search strategy to identify methodological studies in literature databases. Subsequent findings from the review of methodological studies illustrated that reporting practices are the most common aspect of research investigated. Study design names such as ‘methodological review’, ‘systematic review’, and ‘systematic survey’ were often used to describe studies with similar motives, i.e., to synthesize data from previously published research, whether the synthesis approach was quantitative or qualitative. Existing reporting checklists were rarely used, and when used not appended, possibly due to irrelevance of fields oriented to studies with persons. This work demonstrates the necessity and importance of consensus on reporting and nomenclature for making methodological studies more accessible to the health research community.
Methodological studies of the health research literature: Characterizing nomenclature, study designs, and reporting practices
Keywords: methodological studies; research-on-research; research synthesis; literature search methodology; reporting guidelines